JUDGES' CODE OF ETHICS AS THE BASIS OF JUDGES' MORALITY IN ADDRESSING DECISIONS - Mujiyana Mujiyana (Faculty of Law, Universitas Pekalongan, 2023)
Many focus on the performance of judges, and most state that the performance of judges in Indonesia is abysmal, even though their decisions must truly achieve justice as expected by justice seekers. The principle of independence can be bent under the pretext of personal interests. This research aims to analyze the judge's code of ethics as the basis for the judge's morality in sentencing. Research data was obtained through a comprehensive literature study and analysis of related legal documents, including legal texts, government regulations and court decisions relating to the two provinces. After the data was collected, an analytical approach was taken using the legal and constitutional framework as a guide. The research results show that judges deciding a case in court are based on various statutory regulations to underlie and support judges so that they can settle cases submitted to court truly independently and free from interference from any party. This means that statutory regulations honestly guarantee the independence of judges in handling and deciding cases. The judge's morality in examining and deciding every case handled by the court is based on high moral values, both originating from conscience as the most profound whisper of the heart and based on religious teachings. To become a judge so that the resulting decision can be fair and wise, the judge must have a solid spiritual foundation, be honest, and have the courage to take a firm stance.